A practical approach to assess the hazardous exposure potential of investigational drugs. (27th March 2020) - McLeod, E Nicole; Fillis, Cambree J; Blind, Jill E
Abstract: Purpose: A method to evaluate the hazardous exposure potential of investigational drugs was developed in order to comply with hazardous drug handling standards. Summary: New nationwide standards require health-system pharmacies to recognize potential occupational risks and protect employees from any hazardous exposure. United States Pharmacopeia general chapter 800 (USP<800>) provides recommendations on handling precautions for commercial hazardous drugs. Recommendations for investigational drugs are less clear, with USP<800> suggesting more widespread protections when information is deemed insufficient to assess the risk. The investigational drug services pharmacy at a freestanding pediatric hospital developed a method to evaluate the hazardous potential of investigational drugs in order to determine the likelihood that a drug held an occupational handling risk. The goal of the project was to ensure compliance with hazardous drug handling standards and provide adequate employee protection while minimizing the financial burden on the health-system pharmacy. Conclusion: Investigational drugs that meet any of 4 defined criteria should be subject to hazardous drug handling precautions until adequate safety data are available.